Matrix metalloproteinase 7 controls pancreatic acinar cell transdifferentiation by activating the Notch signaling pathway - Sawey, Eric T. (National Academy of Sciences, 2007)
Acinar-to-ductal metaplasia in the pancreas is associated with an increased risk for tumorigenesis. Molecular dissection of this process in vitro has shown that primary acinar cells, in response to EGF receptor ligands, can transdifferentiate into duct-like epithelia, passing through a nestin-positive intermediate, in a Notch pathway-dependent manner. Here, we show that in vitro acinar transdifferentiation depends on matrix metalloproteinase 7 (MMP-7), a proteinase expressed in most metaplastic epithelia in vivo. MMP-7 was found to be required for Notch activation, which leads to dedifferentiation of acinar cells to the nestin-positive transitional cell. Besides being necessary for acinar transdifferentiation, it was found that MMP-7 activity was sufficient to induce the process, indicating that molecular signals capable of initiating MMP-7 expression also have the potential to induce formation of metaplastic epithelia in the pancreas.